2019
DOI: 10.3349/ymj.2019.60.9.864
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic Single Site Surgery for the Treatment of Huge Ovarian Cysts Using an Angiocatheter Needle

Abstract: Purpose The aim of this study was to evaluate the feasibility and safety of laparoendoscopic single site (LESS) surgery using an angiocatheter needle in patients with huge ovarian cysts (diameter ≥15 cm). Materials and Methods Thirty-one patients with huge ovarian cysts underwent LESS surgery using an angiocatheter needle between March 2011 and August 2016. An intra-umbilical vertical incision (1.5–2.0 cm) was made in the midline. After the cyst wall was punctured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Few, heterogeneous reports have been documented in the literature describing similar techniques. Only 5 of these series included cysts of at least 15 cm, as in our series (1)(2)(3)(4)(5)(6). Some of these case series included a larger number of patients, but at the same time, they also included malignant cysts in up to 13% of cases, as described by Ki et al In our opinion, we cannot stress enough the need for strict selection criteria to decrease the risk of an accidental finding of invasive tumor in the final pathological specimen.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Few, heterogeneous reports have been documented in the literature describing similar techniques. Only 5 of these series included cysts of at least 15 cm, as in our series (1)(2)(3)(4)(5)(6). Some of these case series included a larger number of patients, but at the same time, they also included malignant cysts in up to 13% of cases, as described by Ki et al In our opinion, we cannot stress enough the need for strict selection criteria to decrease the risk of an accidental finding of invasive tumor in the final pathological specimen.…”
Section: Discussionmentioning
confidence: 81%
“…Both of these factors can increase the risk of intraoperative spillage because of unintentional cystic rupture. Some case reports have been described in the literature with different surgical techniques to limit possible intra-abdominal spillage, but none of these procedures are suitable for giant cysts occupying the entire abdominal cavity (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…LESS, which produces a hole incision with a length of about 1.5~3.0cm through the umbilicus has a better cosmetic effect compared with traditional laparoscopic surgery [11]. However, due to the destruction of the normal shape of the umbilicus, the scar will be left, more or less [12]. At the same time, the complete incision and suture of the normal structure of the umbilicus may increase the incidence of umbilical incisional hernia [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated the feasibility of SPA laparoscopy for large ovarian tumors. In those studies, surgeons were able to remove tumors with a mean size of 20 cm with SPA laparoscopy (10,12). Almost all patients underwent successful surgery without conversion to laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of SPA laparoscopy illustrated in previous studies, many surgeons remain reluctant to perform a single-port laparoscopic approach for large BOT due to the aforementioned reasons. However, since the introduction of SPA laparoscopy, the advantages of SPA with an extracorporeal approach for large ovarian tumors have been reported in several studies ( 10 12 ). It not only provides better cosmesis, less pain, and faster recovery after surgery but the relatively large umbilical incision created in SPA also facilitates extracorporeal procedures and the removal of bulky specimens with ease.…”
Section: Discussionmentioning
confidence: 99%